Disruption of creative marketing supply chain due to generative artificial intelligence - Evertse, Justin (University of the Witwatersrand, Johannesburg, 2022)
This study explores the transformative impact of generative AI on the creative marketing industry's supply chain process, focusing on the challenges and opportunities presented by AI in content creation. The advent of AI has revolutionised the way content is generated, leading to a paradigm shift in the creative landscape. The study investigated the implications of this shift for creativity, originality, and efficiency within the marketing and advertising sectors. Through a qualitative research methodology, including interviews with various industry stakeholders, this study delved into the nuances of AI's integration into creative processes and its effects on workflow, production, and distribution channels within the creative marketing industry. The research is grounded in theories of disruptive innovation and technology organisation enterprise theory, providing a theoretical framework to analyse the impact of AI technologies on traditional creative and marketing practices. It addresses crucial concerns such as the ownership of AI-generated content, the role of human creativity in the age of AI, and the ethical considerations surrounding AI in creative industries. The study's findings highlight a dual impact: AI as a tool for enhancing creative processes, enabling more efficient and diverse content generation, and AI as a disruptor, challenging traditional roles and workflows within the industry. Significantly, the study identifies a shift towards more collaborative models between AI and human creativity, suggesting that the future of the creative marketing industry lies in leveraging AI to augment human talent rather than replace it. This balance presents opportunities for innovation and new forms of content creation but also necessitates a re-evaluation of skill sets, job roles, and industry standards to adapt to an AI-integrated environment. The research underscores the importance of ethical guidelines and industry-wide discussions on the use of AI, advocating for policies that support creativity, protect intellectual property, and ensure fair competition in the evolving landscape. In conclusion, this qualitative research study provides an insightful analysis of the complex dynamics between generative AI and the creative marketing industry. It offers a comprehensive understanding of the challenges and opportunities AI presents, iii emphasising the need for a strategic approach to integrate AI technologies. By highlighting the potential for AI to augment human creativity and transform supply chain processes, the study contributes valuable perspectives to the ongoing discourse on the future of creativity and technology in marketing and advertising
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Digital business; AI; Disruption; Creative marketing; Supply chain; Suppliers; Providers; Agency; UCTD; SDG-8: Decent work and economic growth